Systematic review of published literature on international humanitarian law from Islamic perspective - Elshobake, Mohammed R. M. (Macrothink Institute, 2025)
Scholars and researchers have discussed rules and principles related to international humanitarian law from Islamic perspective, focusing on three rules and principles: the rules of war and peace, principles for the protection of civilians, and principles for the protection of civilian objects. The primary aim of this study was to systematically review and organize existing research and studies concerning the rules and principles of international humanitarian law from an Islamic perspective. This review followed the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines, identifying and examining relevant literature in the Scopus database. The process involved defining the search criteria, selecting pertinent articles, and analyzing the findings. These findings show that there is a focus on some rules and principles of international humanitarian law from an Islamic perspective, such as principle of peace and war, the principles of proportionality, necessity, and reciprocity, in addition to protection of vulnerable people in armed conflict such as: children and persons with disabilities, and prisoners of war. Nerveless, there is no research on the principles of protecting many types of civilians, such as women, the elderly, workers in the medical sectors, journalists, and media professionals. As well as no research on the principles of protecting many types of civilian objects, such as: medical facilities, educational facilities, places of worship, and press facilities. Therefore, future research should address this gap in the published literature to better grasp the rules of international humanitarian law from Islamic perspective